Pengaruh Kegiatan Ice Breaking Dalam Pembelajaran Terhadap Partisipasi Siswa di SDN Pamindangan - Fadiyah, Firda Hanan; Sunarni, Ani; Sari, Meylinda Ika; Yohana, Esra; Putri, Wafiqazizah Ismi Esa; Putri, Salma Anindya (Peneliti.net, 2024)
Strategies that can be used to make students active and not bored in class is to carry out ice breaking activities in learning. This is a way that aims to provide a more relaxed, happied class atmosphere and attract student participation in classroom learning. The purpose of this research is to determine the effect of ice breaking activities on learning and increase student participation in classroom learning. This research uses a qualitative descriptive research method, with data collection techniques trough observation. Ice breaking activities can help teachers and student in learning. Teachers can organize the class so that it is conducive, students are enthusiastic and happy, and can participate actively in learning.